Elderly caregivers at long-stay institutions: quality of life and temporomandibular dysfunction - Tânia Adas Saliba Rovida; Rosana Leal do Prado; Renata Colturato Joaquim; Luiz Fernando Tano; Cléa Adas Saliba Garbin (Universidade Estadual de Campinas, 2015)
Aim: To assess the profile, quality of life and the presence of Temporomandibular Disorders (TMD) in elderly caregivers. Methods: Thirty-nine caregivers who worked in six long-stay institutions for the elderly in three different municipalities participated in the study. The research instruments were the WHOQOL-BREF, the Fonseca questionnaire and the socio-demographic questionnaire. The Kruskal-Wallis test with the Dunn's correction was performed at a level of 5%. Results: Females accounted for 94.9% of the sample. The average monthly wage was R$ 832.00. The average working week was 39 hours. The WHOQOL dominions showed the following averages: 74.25 Physical; 70.33 Psychological; 65.79 Social Affairs; 58.38 Environment. Mild DTM was present in 43.6% of the caregivers, of which 7.7% were moderate, 5.2% severe, 23.0% of the professionals were asymptomatic and 20.5% did not answer. The association between TMD and the quality of life showed p=0.6752. Conclusions: It was concluded that there was no relationship between the quality of life and symptoms of temporomandibular dysfunction among the caregivers of elderly in this study.